Antibiotic resistance in Helicobacter pylori: Recent insights - D Weerasekara; DMBT Dissanayake; GIDDAD Athukorala; MM Weerasekara; SSN Fernando (Sri Lankan Journal of Infectious Diseases, 2014)
The discovery that Helicobacter pylori (H. pylori) infection is the main cause of most gastro duodenal diseases has dramatically changed the management of these diseases. Antibiotics are the mainstay of treatment. However, prevalence of H. pylori antibiotic resistance is increasing worldwide, and is the main factor affecting the efficacy of current therapeutic regimens. In Sri Lanka, although eradication therapy for H. pylori by antibiotics is commonly advocated, due to a lack of susceptibility data, it has not been possible to formulate suitable guidelines for clinical use. DOI: http://dx.doi.org/10.4038/sljid.v4i1.5986